2022
DOI: 10.3389/fpsyg.2021.712330
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Types of Intelligence and Its Implicit Theories Vary Based on Gender and Grade Level?

Abstract: The current study investigated correlations among gifted students’ academic performance; emotional, social, analytical, creative, and practical intelligence; and their implicit theories of intelligence. Furthermore, it studied the effect of gender and grade on these variables. The participants included 174 gifted fifth (41.4%) and sixth (58.6%) grade students, comprising 53.4% male and 46.6% female. The following analytical, creative, and practical intelligence tests were administered: Aurora Battery, the emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 117 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…The topic of gender differences in human abilities remains a fertile area of study in educational, psychological, physiological, and neuroscientific research (Abraham, 2016; Feingold, 1992; Hedges & Friedman, 1993; Kogan, 1974). In psychology, the emphasis is on the study of gender differences in intellectual abilities, such as spatial abilities (e.g., Syzmanowicz & Furnham, 2011), memory (e.g., Hill et al, 2014), intelligence (e.g., Ayoub et al, 2021; Dai & Lynn, 1994), and creativity (Baer & Kaufman, 2008). A literature search of gender differences in human cognition revealed hundreds of works devoted to: (a) examination of possible gender differences in these and other intellectual abilities, and (b) explanations of gender differences when the findings showed that one gender had an advantage over another in one or more.…”
Section: Gender Difference In Creative Potential: a Comparison Of Dt ...mentioning
confidence: 99%
“…The topic of gender differences in human abilities remains a fertile area of study in educational, psychological, physiological, and neuroscientific research (Abraham, 2016; Feingold, 1992; Hedges & Friedman, 1993; Kogan, 1974). In psychology, the emphasis is on the study of gender differences in intellectual abilities, such as spatial abilities (e.g., Syzmanowicz & Furnham, 2011), memory (e.g., Hill et al, 2014), intelligence (e.g., Ayoub et al, 2021; Dai & Lynn, 1994), and creativity (Baer & Kaufman, 2008). A literature search of gender differences in human cognition revealed hundreds of works devoted to: (a) examination of possible gender differences in these and other intellectual abilities, and (b) explanations of gender differences when the findings showed that one gender had an advantage over another in one or more.…”
Section: Gender Difference In Creative Potential: a Comparison Of Dt ...mentioning
confidence: 99%